(untitled) (International Journal of Engineering and Computer Science, 2017)
Watermark is embedded by modifying the third level mid frequency coefficients of the host image with multiple SFs. As many combinations of SFs are possible, it is difficult to obtain optimal solutions by trial and error method. Hence, in order to achieve the highest possible transparency and robustness, optimization of the scaling factors is necessary. This task employs Genetic Algorithm (GA) to obtain optimum SFs. GA can search for multiple solutions simultaneously over a wide range, and an optimum solution can be gained by combining the obtained results appropriately. The aim of the task is to develop an optimal watermarking technique based on DWT domain for grey-scale images. In this paper, a robust and oblivious image watermarking algorithm using maximum wavelet coefficient modulation is proposed. Simulation results show that performance of the proposed method is superior in terms of Peak Signal to Noise Ratio (PSNR) and Normalized Correlation Coefficient (NCC).